Combination of rehydrated sodium caseinate aqueous solution with blackcurrant concentrate and the formation of encapsulates via spray drying and freeze drying: Alterations to the functional properties of protein. Issue 5 (9th March 2021) - Wu, Gang; Hui, Xiaodan; Brennan, Margaret A.; Zeng, Xin‐An; Guo, Xinbo; Brennan, Charles S.
Abstract: The practical applications of protein ingredients in the preservation of bioactive compounds are of research interest. In this study, an aqueous solution of sodium caseinate was combined with blackcurrant concentrate to produce novel protein ingredients using spray‐drying and freeze‐drying techniques. High‐performance liquid chromatography results showed that both spray‐drying and freeze‐drying strategies effectively delivered the anthocyanins of blackcurrant concentrate. Cyanidin and delphinidin contents in spray‐dried samples 71.39 ± 1.07 μg/g and 83.55 ± 1.04 μg/g, respectively, while in the freeze‐dried sample, cyanidin and delphinidin contents were at 53.61 ± 0.13 μg/g and 59.55 ± 0.54 μg/g, respectively. The physical and functional properties of sodium caseinate ingredients were altered by both drying strategies and also through the addition of blackcurrant concentrate. Drying processes influenced the shape and size of particles, and ultimately altered the rehydration properties of the protein ingredients. The inclusion of blackcurrant concentrate for sodium caseinate ingredients and the spray‐and freeze‐drying strategies altered the physical properties (particle size distribution, bulk density, and morphology), functional properties (water‐holding capacity, oil‐holding capacity, foamability, and foam stability), and nutritional values of sodium caseinate ingredients, providing new options for the development and innovation of food products. Novelty impact statement: The research is novel in generating sodium caseinate‐based blackcurrant concentrate encapsulates by spray‐drying and freeze‐drying. This research advances current understanding by illustrating the modifications in protein functional properties, while maintaining bioactivity. The research could be applied in generating novel food systems for health enhancement.